The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1990
DOI: 10.1099/0022-1317-71-11-2665
|View full text |Cite
|
Sign up to set email alerts
|

The production of human parvovirus capsid proteins in Escherichia coli and their potential as diagnostic antigens

Abstract: We have expressed a number of polypeptides derived from the capsid proteins of the human parvovirus B 19 in Escherichia coli. These include native VP1 (8410 and VP2 (58K) proteins and also fusions to flo galactosidase containing differing amounts of the amino terminus of the VP1/2 polypeptide. Although each of these was expressed at high levels and the majority were produced as full-length proteins, only one was soluble. This soluble polypeptide, p132, is a/3-galactosidase fusion protein that includes 145 amin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
1

Year Published

1992
1992
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 31 publications
(20 reference statements)
1
11
0
1
Order By: Relevance
“…This was surprising in comparison with the other human-pathogenic parvovirus, B19, in which the VP1u is very immunoreactive [30] and contains many neutralizing epitopes [31][32][33][34][35]. Indeed, both VP2 and the VP1u region have been successfully used in the diagnosis of B19 infections [30,[36][37][38]. One possible reason for the dissimilarity between the 2 viruses might be a difference in the location of VP1u within the capsid [34,39,40], which could affect its accessibility to host immunity.…”
Section: Discussionmentioning
confidence: 96%
“…This was surprising in comparison with the other human-pathogenic parvovirus, B19, in which the VP1u is very immunoreactive [30] and contains many neutralizing epitopes [31][32][33][34][35]. Indeed, both VP2 and the VP1u region have been successfully used in the diagnosis of B19 infections [30,[36][37][38]. One possible reason for the dissimilarity between the 2 viruses might be a difference in the location of VP1u within the capsid [34,39,40], which could affect its accessibility to host immunity.…”
Section: Discussionmentioning
confidence: 96%
“…Symmetry considerations (7) and the assumption that the basic residues on VPl help stabilize the viral DNA led to the prediction that VPl folds inside the viral capsid, and only the amino terminus of VP2 would enter the cylinders. We (17), and later others (18), have demonstrated that specific reactivity to the VPl unique region develops during natural infection and that VP1 is the dominant species recognized by convalescent human serum (17 parvoviruses have been mapped to regions ofVP2 (20), making this a more likely area for receptor binding in these structurally similar viruses. Either as a membrane contact region or receptor ligand, VP I would be expected to be an efficient target for neutralizing antibody.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, its incorporation into serological assays was thought essential (Rayment et al, 1990). However, it is now clear that this observation, which was based on the absence of antibodies to linear epitopes within the VP2 protein, when screened by Western blot, is erroneous.…”
Section: Antibody-mediated Immune Responsementioning
confidence: 99%